2020
DOI: 10.1080/14459795.2020.1826559
|View full text |Cite
|
Sign up to set email alerts
|

Defining the esports bettor: evidence from an online panel survey of emerging adults

Abstract: Competitive video gaming (esports) is a growing multinational , billion-dollar industry. Esports cultures replicate traditional sports cultures, involving elite athletes, teams, league sponsorships, large viewing audiences, high profile leagues and championships, and opportunities to bet on outcomes. However, little is known about people who bet on esports, it is generally considered a niche practice. Using data from the Emerging Adults Gambling Study, a nonprobability survey of 3549 people aged 16-24 living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 23 publications
(26 reference statements)
9
38
1
Order By: Relevance
“…Esports bettors were found to be highly involved in other video game-related gambling activities (i.e., skin gambling) and traditional forms of gamblingmost frequently sports betting (around 70%), followed by casino table games, private betting for money, EGMs, and Australian lotteries. These findings add to the growing evidence from previous studies which compared adult esports bettors to sports bettors (Gainsbury et al, 2017b) and youth sample (16-24 years) esports bettors versus those betting on other sports (Wardle et al, 2020). Compared to sports bettors, esports bettors more frequently gambled on 'riskier' traditional gambling activities (i.e., where large amounts of money can be spent in short periods of timenamely casino table games, EGMs, and private betting for money).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Esports bettors were found to be highly involved in other video game-related gambling activities (i.e., skin gambling) and traditional forms of gamblingmost frequently sports betting (around 70%), followed by casino table games, private betting for money, EGMs, and Australian lotteries. These findings add to the growing evidence from previous studies which compared adult esports bettors to sports bettors (Gainsbury et al, 2017b) and youth sample (16-24 years) esports bettors versus those betting on other sports (Wardle et al, 2020). Compared to sports bettors, esports bettors more frequently gambled on 'riskier' traditional gambling activities (i.e., where large amounts of money can be spent in short periods of timenamely casino table games, EGMs, and private betting for money).…”
Section: Discussionsupporting
confidence: 66%
“…Common risk factors associated with experiencing harm due to traditional gambling activities include, but are not limited to: being male, young, and from low socio-economic status backgrounds; gambling with greater intensity (e.g., more activities, greater frequency, greater expenditure); and early exposure to gambling (Abbott et al, 2018;Miller, 2015). Many of the common risk factors associated with traditional gambling (being young, male, greater gambling intensity) also appear to be associated with esports betting (Abarbanel, Macey, Hamari, & Melton, 2020;Gainsbury, Abarbanel, & Blaszczynski, 2017a, 2017bGambling Commission, 2018, 2019Macey & Hamari, 2018a;Rockloff et al, 2020;Wardle, Petrovskaya, & Zendle, 2020). In addition to being male and younger, an Australian study found other distinct demographic differences between esports bettors and sports bettors (Gainsbury et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations